Análise do impacto térmico e mecânico na secagem de sementes de maracujá - Fedrizzi, Pedro Gobbo (Universidade Federal de São Carlos, 2024)
Brazil leads the global production of passion fruit, a fruit rich in vitamin C, magnesium, potassium, and vitamin A. Additionally, its oil has antioxidant properties, making it valuable in both the food and pharmaceutical industries. The seeds are preferably harvested at their physiological maturity, with maximum germinative power. However, when there is excess moisture, the hilum (where water flow occurs) of the seed can be damaged, allowing microbiological contamination, such as fungal infections. Thus, drying is essential to maintain the physiological qualities of the seed. In this study, 10 drying processes of passion fruit seeds were carried out, using both fixed and fluidized bed drying methods, to determine the best drying conditions for the seeds. Each drying process began with an initial seed mass of 50 grams and was completed when the sample reached its equilibrium moisture content. The variables analyzed were temperature (40,9; 45,0; 55,0; 65,0 and 69,1ºC) and air flow rate (0,8; 1,7; 3,9 and 7,1 m³/min). The dried seeds were also subjected to a physical characterization by imaging. Diffusivity was calculated using Fick's second law for each experiment, and the drying curves were fitted using the Henderson and Pabis, Newton, Page, Overhults, two-term, and exponential models to determine the conditions in which their adjustment coefficients presented maximum values. The seeds showed good homogeneity among themselves. In drying, the fluidized bed yielded better results compared to the fixed bed, and temperature had a greater influence than air flow rate on drying time. The diffusivity model used did not fit the drying data well, and the two-term model provided the best fits.
Analysis of thermal and mechanical effects on passion fruit seeds drying
Keywords: Passiflora edulis f. flavicarpa; Secagem; Leito fixo; Leito fluidizado; Curvas de secagem; Drying; Fixed bed; Fluidized bed; Drying curves; ENGENHARIAS::ENGENHARIA QUIMICA::OPERACOES INDUSTRIAIS E EQUIPAMENTOS PARA ENGENHARIA QUIMICA